A new N-containing phenolic glycoside from Capsicum annuum L. Issue 2 (17th January 2022) - Song, Changwei; Yu, Changyan; Zhu, Xinting; Luo, Xirong; Zhang, Yong; Meng, Lingjie; Luo, Yong; Chang, Han; Qin, Cheng; Liu, Yun
Abstract: A new N -containing phenolic glycoside (1 ) and seven known compounds were isolated from the fruits of Capsicum annuum L. Their structures were elucidated by extensive spectroscopic methods including MS, 1D and 2D NMR (HSQC, HMBC, 1 H- 1 H COSY, etc.). The stereo configuration of the new compound was determined by comparison of the experimental and calculated electronic circular dichroism (ECD) spectra. Compounds 1–8 were evaluated in vitro for their cytotoxic activities against HCT-116 cell line using Sulforhodamine B (SRB) assay, and the result showed only compound 6 displayed a weak inhibitory activity against HCT-116 (IC50 = 22.5 ± 3.3 mmol/mL). Abstract : UF0001